Gender-Related Facial Surgical Goals - Somenek, Michael (Facial Plastic Surgery, 2018)
In the last several years, there has been an increasing demand for surgical facial feminization or masculinization to treat the gender dysphoric patient. However, while aesthetic ideals for facial rejuvenation are well described and taught, there is a relative paucity of literature on how to achieve a feminine or masculine morphology. It is thus becoming increasingly important for facial plastic surgeons to understand patient goals regarding facial feminization or masculinization, and to have a systematic approach for analyzing the female and male face.
Keywords: facial analysis; facial feminization; facial masculinization; gender analysis